Analisis Penerapan Good Corporate Governance Dalam Meningkatkan Kinerja Karyawan Pada Bank Syariah Indonesia Cabang Stabat - Mulya Anjani, Tira; Sani, Abdullah; Hasanah, Nurul (-, 2023)
The implementation of Good Corporate Governance is carried out by taking into account aspects of employee performance, namely conducting training to improve employee skills functionally, training employees to work together as a team. Based on the results of the above observations, it can be seen that the implementation of Good Corporate Governance has been carried out properly by the Stabat Branch of Bank Syariah Indonesia. So, to describe the implementation of Good Corporate Governance in improving employee performance, the authors are interested in proposing a research title, namely "Analysis of the implementation of Good Corporate Governance on employee performance at PT. Bank Syariah Indonesia Stabat Branch Period 2021-2022”. This background made the researchers formulate the purpose of this study, namely to find out the application of Good Corporate Governance in improving employee performance at PT. Bank Syariah Indonesia Stabat Branch for the 2021-2022 period. The research method used in this study is a qualitative research method using data collection techniques through observation, interviews and documentation with data analysis techniques through data collection, data reduction, data presentation and concluding or verifying data. After carrying out all the steps mentioned above, the results of this study can be concluded that there is a positive relationship from the implementation of Good Corporate Governance which will produce a good work culture so that company goals will be easier to achieve. A good work culture will be able to build a dynamic and professional work environment for BSI KCP employees. stabat